Mechanism of the Transmetalation of Organosilanes to Gold. Issue 1 (10th September 2015) - Falivene, Laura; Nelson, David J.; Dupuy, Stéphanie; Nolan, Steven P.; Poater, Albert; Cavallo, Luigi
Abstract: Density functional theory (DFT) calculations were carried out to study the reaction mechanism of the first transmetalation of organosilanes to gold as a cheap fluoride‐free process. The versatile gold(I) complex [Au(OH)(IPr)] permits very straightforward access to a series of aryl‐, vinyl‐, and alkylgold silanolates by reaction with the appropriate silane reagent. These silanolate compounds are key intermediates in a fluoride‐free process that results in the net transmetalation of organosilanes to gold, rather than the classic activation of silanes as silicates using external fluoride sources. However, here we propose that the gold silanolate is not the active species (as proposed during experimental studies) but is, in fact, a resting state during the transmetalation process, as a concerted step is preferred. Abstract : Studying silanolates : Upon reaction with silanes, the gold(I) complex [Au(OH)(IPr)] allows access to various gold silanolates. These silanolates are key intermediates in a fluoride‐free process that results in the net transmetalation of organosilanes to gold. Here, using density functional theory (DFT) calculations, we propose that the gold silanoate is not the active species, but is in fact a resting state during the transmetalation process, as a concerted step is preferred.